Multimedia Integration of Mathematical Internet Memes into Mathematics Classrooms in Secondary School Curriculum - Mutua, Dominic Mutuku; Mwangi, Waweru (International Journal of Membrane Science and Technology, 2023)
Mathematics is a core subject in almost all secondary education curricula. In improving performance in mathematics, there is a need to consider developing new teaching and learning pedagogies that tap the students’ interests and enhance the classroom environment. This study focuses on integrating mathematical internet memes into mathematics classrooms to determine their effect on students’ performance, understanding, engagement, motivation, and excitement. It also examines memes’ impact on learning experiences, the potential to provide alternative formative assessments and investigate students’ readiness to learn with memes in the mathematics classroom. The study revealed that integrating mathematics internet memes in the mathematics classroom has no significant impact on student’s performance in mathematics. Moreover, research showed experiment group performance in meme-aided and traditional assessment tests was statistically similar, indicating that both tests provide identical feedback on students’ performance. The study further revealed that integrating memes in the mathematics classroom improves students’ engagement, motivation, and excitement in the mathematics classroom.